An analysis of stone circle site structure on the Pawnee National Grassland, Weld County, Colorado - Long, Jennifer K., author; LaBelle, Jason, advisor; Sibold, Jason, committee member; Ore, Janet, committee member (Colorado State University. Libraries, 2011)
The purpose of this research is to create a context of stone circle site information on the Pawnee National Grassland that will contribute to the overall study of this valuable resource within Colorado, as well as throughout the Great Plains region. These data will provide a solid base for future research to be conducted on stone circles in Colorado. In order to better understand stone circle site structure, cluster analysis was utilized to expose patterns for three analyses which included overall site structure based on the landforms on which the site resides, stone circle gap direction as compared to overall site structure, and comparing prevailing wind directions and the portion of the stone circles with the highest stone counts. To accomplish this, center points were collected with a GPS unit for each of the 249 stone circles recorded. Attributes were then documented including exterior diameters, circle definition, gap direction, stone counts per octant, and associated artifacts and features. To determine overall site structure, nearest neighbor analysis was run in ArcGIS 9.3 yielding a spatial pattern of clustered, dispersed, or random. Next, an attribute was included in the cluster analysis using the spatial autocorrelation test with the gap direction in degrees. This analysis also yielded a result of clustered, dispersed, or random. Finally, for the wind direction analysis, rose diagrams were created to compare each stone circle feature with the prevailing wind directions. The findings for the site structure based on landform types consisted of the lowland sites being random in pattern, or consisting of less than three features. The midland sites were dispersed, and the highland sites were clustered or random. When comparing overall site structure with the direction of the gap, the random and clustered sites had a random pattern for gap direction. The dispersed site, however, had a clustered pattern. The clusters consisted of three stone circles facing the same direction, though each cluster faced a different direction. Finally, the result for prevailing wind direction and the highest stone counts was inconclusive. Additional research is necessary to provide more conclusive interpretations of this analysis.